The geometry on the slope of a mountain - P. Chansri; P. Chansangiam; Sorin V. Sabau (My University, 2020)
The geometry on a slope of a mountain is the geometry of a Finsler metric, called here the slope metric.We study the existence of globally defined slope metrics on surfaces of revolution as well as the geodesic's behavior.A comparison between Finslerian and Riemannian areas of a bounded region is also studied.
Keywords: Advanced Differential Geometry Research